Comparative study of nuclear models with Experimental data for Heavy Radioactive Nuclei ((_91^231)Pa ,(_90^232)Th) - Merzaee, Dowood (Journal of Natural Sciences – Kabul University, 2025)
Usually, advanced forms of the Thomas Fermi model are used to study the properties of heavy cores. In this paper, some of the properties of radioactive nuclei , in the liquid droplet model with Thomas Fermi model are investigated and compared with experimental data. By adding the deformation energy correction sentence to the nuclear state equation, the parameters of the nuclear models are obtained, which can be used to study the nuclear properties such as the height of the fission bond. Also, the values obtained from the calculations are compared with the values of experience. This comparison shows that using this method, the cleavage of deformed heavy nuclei can be studied. Also, using the exact coefficients of nuclear models, the thermodynamic quantities of radioactive heavy nuclei ( ) Th were calculated and compared with experimental values.